Rebranding of Arnetta Craft’s product in Malaka Sari, East Jakarta - Agustina Dwianti; Afourli Daven Tamboto; Alya Gustriani Syafitri; Angeline Calista Slamet; Anisa Larasati; Ativa Kannuri Nada; Baharini Kurnia Putri; Epseen Epseen; Jarell Ong; Leo Andri Yulius Caesar; Nadia Ingrida Winata; Nikolas Ermando; Nuril Kusumawardani Soeprapto Putri; Ricky Prasojo; Safira Fauzia Rahma; Sevenpri Candra; Sheren Kristianti; Sulistyo Heripracoyo; Sulthan Bahariawan; Syamila Karima; Wenny Carnika; Zidan Febrian (Community Empowerment, 2021)
The role of society is very important in maintaining the balance of nature. The community empowerment approach is the success key in educating the surrounding environment. Arnetta Craft is a community empowerment presenting in Malaka Sari, East Jakarta. Arnetta Craft continuously invites all levels of society caring about the results of household waste, especially used cooking oil. Processed products from household waste produce a useful product for people's daily needs and have commercial selling value. However, with the existing competition, the marketing approach needs to be improved by creating logos, labeling and product packaging. To be able to produce logos, labeling and product packaging, a structured interview was conducted with the owner of Arnetta Craft. At the end of the activity, new logos, labeling and packaging have been produced used as product rebranding.